DEVELOPING ENGLISH SYLLABUS FOR KINDEGARTEN STUDENTS - Emmi Naja (Jurnal Bahasa Lingua Scientia, 2011)
Many kindegarten start to introduce English as their local content subject, but most of them are did not provide the English syllabus. This study suggest to kindegarten teacher in developing English syllabus for kindegraten students, in order to they have any standart in teaching English. The model of development is adapted from the framework component of syllabus that is conveyed by Grave. This model consist of seven steps, they are: need assesment, determining goals and objectives, conceptualizing content, selecting and developing materials and activities, organization of content and activities, eveluation, and consideration of resources and constraints.